Elative and excessive in Lithuanian: daũg ‘much’ and per̃ daũg ‘too much’ - Petit, Daniel (Baltistica, 2024)
The Baltic quantifier *daugi is usually derived from a PIE root *dhegh- ‘to make, to produce’, although its formation, as a substantivized adjective or a noun, remains problematic. In this article, I attempt to determine the original function of the quantifier. To achieve this goal, it is necessary to compare the elative sense (‘very much’) and the excessive sense (‘too much’). The excessive is expressed in Lithuanian by the adverb per̃ (e.g. per̃ dìdelis ‘too big’). It can be assumed that the form *daugi was first introduced in argumental functions, which the adverb *per(i)- was unable to fulfill, before the latter switched to the excessive sense.